Exporting Hyperinflation: The Long Arm of Chiang Kai-shek - Richard C.K. Burdekin; Hsin-hui I. H. Whited (Claremont McKenna College, Department of Economics, 2001)
As mainland China's inflationary spiral accelerated in 1947-1949 there was a massive outflow of funds to the island of Taiwan. The exporting of China's hyperinflation was facilitated by the fixed, overvalued, exchange rate between the mainland Chinese currency and the Taiwanese currency that was adopted in August 1948. Empirical tests offer support for the importance of the 1948 monetary policy reform and suggest a substantial impact of capital inflows and excess money growth in mainland China on inflationary pressures in Taiwan. We find no independent role for Taiwanese money growth in the inflation process.
Keywords: E31; E65; F42; N15; 330